KEPEMIMPINAN TRANSFORMASIONAL DI LEMBAGA PENDIDIKAN (Kajian Sejarah, Psikologis dan Pandangan Islam Tentang Kepemimpinan) - Rahman, Syaifur (Humanistika : Jurnal Keislaman, 2017)
Abstract: educational institution is an institution that has a big responsibility because it is a non-profit agency. Though education is a primary need of every human being, with education, people will have the opportunity to live a better life, in addition to the education as well as the vanguard (Avand - garde) a nation, therefore, educational institutions should be designed in accordance with the conditions of the community. But until now the institution is often used as a tool to perpetuate the domination and hegemony of one group against another group.Royal tradition that tends dictator inherited presumably still is no exception in the world of education. Massive power holders often selfish personal interests of the public interest. Though progress and development of an institution is strongly influenced by its leaders. For the presence of leaders who can turn potential into energy is a necessity that must be owned by an agency to be able to abolish the status quo. The leader of the transformative spirit does not come from those who bernasab great leaders or given, but this leader is someone who is always learning, striving, and have lofty ideals for the sake of fighting for humanity. Keywords: Leader, Transformational, education.